STANDAR IZIN TEMPAT USAHA RITEL ALFAMART OLEH BADAN PELAYANAN TERPADU DAN PENANAMAN MODAL (BPTPM) KOTA PEKANBARU - Adhadiansyah, Junrian; Yuliani, Febri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Alfamart is a retail business which is began to grow rapidly and currently has many outlets in Pekanbaru city. Therefore, the Agency of Integrated Services and Investment (BPTPM) of Pekanbaru city as the agencies that implement the business premises licensing service have to provide license according to standards that have been established so that retail business Alfamart does not give any adverse impact to minimarkets that belongs to local communities or other small business nearby.This research is conducted to observe how the Agency of Integrated Services and Investment (BPTPM) of Pekanbaru city implement the standard and factors that affected the implementation of license’s standard of retail business Alfamart. In order to look for the result that will be discussed, this research uses the following indicators: specialization of work, chain of command, control range, and formalization. This research uses qualitative descriptive approach with data collecting technique interview, observation, and documentation.The result of this research is that the implementation of license’s standard of retail business Alfamart by the Agency of Integrated Services and Investment (BPTPM) of Pekanbaru city is overall still not good enough seen from specialization of work, chain of command, control range, and formalization. Although the task was already divided evenly and suitable to the field of each agency. The affecting factors are lack of human resources to execute the work, obstacle in coordination, difficulty of monitoring and license’s standard of business premises that is still unclear.Keywords: License’s Standard of Business Premises, Alfamart, the Agency of Integrated Services an Investment (BPTPM).